Extreme ultraviolet spectroscopy and atomic models of highly charged heavy ions in the Large Helical Device. (18th October 2016) - Suzuki, C; Murakami, I; Koike, F; Tamura, N; Sakaue, H A; Morita, S; Goto, M; Kato, D; Ohashi, H; Higashiguchi, T; Sudo, S; O'Sullivan, G
Abstract: We report recent results of extreme ultraviolet (EUV) spectroscopy of highly charged heavy ions in plasmas produced in the Large Helical Device (LHD). The LHD is an ideal source of experimental databases of EUV spectra because of high brightness and low opacity, combined with the availability of pellet injection systems and reliable diagnostic tools. The measured heavy elements include tungsten, tin, lanthanides and bismuth, which are motivated by ITER as well as a variety of plasma applications such as EUV lithography and biological microscopy. The observed spectral features drastically change between quasicontinuum and discrete depending on the plasma temperature, which leads to some new experimental identifications of spectral lines. We have developed collisional-radiative models for some of these ions based on the measurements. The atomic number dependence of the spectral feature is also discussed.